AUTOMATIC ACTIVE PHASE SELECTOR FOR SINGLE PHASE LOAD FROM THREE PHASE SUPPLY - Kumaraswamy, K.; Ashok, L.; Pooja, N.; Akshith, B. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Phase absence is a very common and severe problem in any industry, home or office. Many times one or two phases may not be live in three phase supply. Because of this, many times, some electrical appliances will be on in one room and OFF in another room. This creates a big disturbance to our routine work.This project is designed to check the availability of any live phase, and the load will be connected to the particular live phase only. Even a single phase is available, and then also, the load will be in ON condition.This project is designed with Arduino MCU. This controller continuously checks for live condition of all phases connected to it, and the controller connects the load to the active phase using a Relay. This relay is driven with a transistor. If two or three phases are live, the load will be connected to phase I only. An LCD is provided to display the status of the phase condition. Contrast control preset is given for LCD contrast control. This project uses regulated 12V, 500mA power supply. 7805 three terminal voltage regulator is used for voltage regulation. Bridge type full wave rectifier is used to rectify the ac out put of secondary of 230/12V step down transformer.